Flexibility in Problem Solving: Analogical Transfer of Tool Use in Toddlers Is Immune to Delay - Bobrowicz, Katarzyna; Lindström, Felicia; Lindblom Lovén, Marcus; Psouni, Elia (Frontiers in Psychology, 2020)
Solving problems that are perceptually dissimilar but require similar solutions is a key skill in everyday life. In adults, this ability, termed analogical transfer, draws on memories of relevant past experiences that partially overlap with the present task at hand. Thanks to this support from long-term memory, analogical transfer allows remarkable behavioral flexibility beyond immediate situations. However, little is known about the interaction between long-term memory and analogical transfer in development as, to date, they have been studied separately. Here, for the first time, effects of age and memory on analogical transfer were investigated in 2–4.5-olds in a simple tool-use setup. Children attempted to solve a puzzle box after training the correct solution on a different looking box, either right before the test or 24 h earlier. We found that children (N = 105) could transfer the solution regardless of the delay and a perceptual conflict introduced in the tool set. For children who failed to transfer (N = 54) and repeated the test without a perceptual conflict, the odds of success did not improve. Our findings suggest that training promoted the detection of functional similarities between boxes and, thereby, flexible transfer both in the short and the long term.